The Settlement Requirement in General Assistance - Daniel R. Mandelker (Washington University Law Quarterly, 1956)
Settlement, a statutory residence period which usually must be coupled with an intent to make the locality in question a home, is ordinarily a prerequisite to the receipt of general assistance. The first part of this article traced the history and development of this requirement and outlined the law applicable to the acquisition of a settlement. In the remaining portion attention will be directed to the limitations on the acquisition of a settlement and to the application of settlement rules in the family situation.